1977
DOI: 10.1136/gut.18.8.636
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind clinical trial on gastroduodenal ulcer healing with prostaglandin E2 analogues.

Abstract: SUMMARY Seventy-seven patients with gastroduodenal ulcer were treated with two methyl-prostaglandin E2 analogues, m-PGE2, in a double-blind clinical trial. Each of three groups was given 15 S-15 methyl PGE2 methyl ester, 15 R-15 methyl PGE2 methyl ester, and placebo, respectively. Both forms of m-PGE2 analogues appeared to reduce gastric acid secretion, to shorten ulcer healing, and also to produce some side-effects, form 'S' being the more potent. Prompt healing of the ulcer with these agents did not prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(5 citation statements)
references
References 13 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…However, prostaglandin F compounds are secreted in smaller quantities than PGE and have been reported as either not inhibiting gastric secretion (Robert et al, 1967) or having a weak or transitory effect (Newman et al, 1975;Baker et al, 1978a). ' Administration of PGE has been shown to prevent the formation of gastroduodenal ulcers in several animal models Lee et al, 1973) and has been used to treat peptic ulcers in man (Fung et al, 1974;Fung and Karim, 1976;Gibinski et al, 1977). Hinsdale et al (1974) have reported that duodenal ulcer patients have lower concentrations of PGE in their plasma and basal gastric juice than have normal controls, and it has been suggested that prostaglandin deficiency may be an important aetiological factor in peptic ulcer disease (Robert, 1975).…”
mentioning
confidence: 99%
“…However, prostaglandin F compounds are secreted in smaller quantities than PGE and have been reported as either not inhibiting gastric secretion (Robert et al, 1967) or having a weak or transitory effect (Newman et al, 1975;Baker et al, 1978a). ' Administration of PGE has been shown to prevent the formation of gastroduodenal ulcers in several animal models Lee et al, 1973) and has been used to treat peptic ulcers in man (Fung et al, 1974;Fung and Karim, 1976;Gibinski et al, 1977). Hinsdale et al (1974) have reported that duodenal ulcer patients have lower concentrations of PGE in their plasma and basal gastric juice than have normal controls, and it has been suggested that prostaglandin deficiency may be an important aetiological factor in peptic ulcer disease (Robert, 1975).…”
mentioning
confidence: 99%
“…Coupling these antisecretory effects with previously demon strated cytoprotective effects (15,16), the potential value of orally administered arbap rostil for the treatment of peptic ulcer in cli nical settings (17)(18)(19)(20) is clear.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 12 ] Additionally, PGE 2 has been used to treat gastric ulcer in spite of high price and low efficacy. [ 13 14 ] Therefore, PGE 2 elevation using 15-PGDH inhibitor would be valuable for the management disease that required elevated PGE 2 , like wound healing. Wound healing is a complicated process in human or animal in which skin or another organ-tissue repair itself after having wound.…”
Section: Introductionmentioning
confidence: 99%